The turbulent fragmentation of the interstellar medium: the impact of metallicity on global star formation - Walch, Stefanie; Wünsch, R.; Burkert, A.; Glover, Simon; Whitworth, A. (The astrophysical journal, 2011)
We study the influence of gas metallicity, turbulence, and non-equilibrium chemistry on the evolution of the two-phase interstellar medium (warm and cold atomic phases), and thereby constrain the initial conditions for star formation prevailing in turbulent gas. We perform high-resolution simulations in three dimensions, including a realistic non-equilibrium treatment of the ionization state of the gas, and examine both driven and decaying turbulence. This allows us to explore variations in the metallicity Z. In this paper, we study solar metallicity, Z = Z☉, and low-metallicity, Z = 10−3 Z☉, gas. For driven, large-scale turbulence, we find that the influence of the metallicity on the amount of mass in the cold gas component is small. However, in decaying turbulent conditions this picture is much changed. While cold regions survive in the case of solar metallicity, they are quickly heated and dispersed in low-metallicity gas. This result suggests that star formation can be suppressed in environments of low metallicity, unless a strong turbulent driver is acting on timescales shorter than a few turbulent crossing times. Inter alia this finding could explain the overall inefficient star formation as well as the burst-like mode of star formation found in metal-poor, gas-rich systems like dwarf galaxies.
Gesehen am 04.11.2022